Beginning SQL Queries - Churcher, Clare (Apress, 2012)
As a query language, SQL is really quite small and should be easy to learn. A few basic ideas and a handful of keywords allow you to tackle a huge range of queries. However, many users often find themselves completely stumped when faced with a particular problem. You may find yourself in that group. It isn’t really a great deal of help for someone to say, “This is how I would do it.” What you need is a variety of ways to get started on a tricky problem. Once you have made a start on a query, you need to be able to check, amend, and refine your solution until you have what you need.